2016
DOI: 10.1259/bjr.20150831
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses received in the United Kingdom breast screening programme in 2010 to 2012

Abstract: Changes in the radiation dose in breast screening over time have been determined. Specifically, the impact on radiation dose of introducing different types of DR and computed radiography system into breast screening has been quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 14 publications
11
34
0
2
Order By: Relevance
“…Literature data indicate that mean MGD values for DR systems are about 32% lower than for SF systems, and those for CR systems are close to the values for SF systems [12]. Young et al showed that MGD values for DR systems were lower by 25% than those for SF systems [13]. Similar results have been shown by Hendrik et al [14].…”
Section: Resultssupporting
confidence: 59%
“…Literature data indicate that mean MGD values for DR systems are about 32% lower than for SF systems, and those for CR systems are close to the values for SF systems [12]. Young et al showed that MGD values for DR systems were lower by 25% than those for SF systems [13]. Similar results have been shown by Hendrik et al [14].…”
Section: Resultssupporting
confidence: 59%
“…Figure 17 shows the variation of the MGD for standard mammography with breast thickness based on a large United Kingdom survey of data from 419 X-ray sets over the period 2010–2012 (Young and Oduko, 2016). The data illustrate well the decrease in dose when changing from screen-film to DR systems, and that the dose for the CR systems included in the survey was higher than that for screen-film.…”
Section: Results Of Breast Dose Measurementmentioning
confidence: 99%
“…Regarding radiation dose, studies have reported increased radiation dose with increased compressed breast thickness. [27][28][29] Further, the compression force might influence reattendance. 5,6 However, subsequent reattendance is complex and is affected by several factors rather than simply the level of pain experienced during the screening examination.…”
Section: Discussionmentioning
confidence: 99%